Assessing fluctuation of ant populations in a distinct ecological habitat to track climate change effects - Waqar Majeed; Masud Khawaja; Naureen Rana (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Majeed W, Khawaja M, Rana N. 2021. Assessing fluctuation of ant populations in a distinct ecological habitat to track climate change effects. Biodiversitas 22: 2722-2727. Ants are an indicative group of terrestrial invertebrates that play an important role in soil fertility by clearing the soil surface of vegetation. This study focuses on the composition and structure of ant communities in two sampling stations: Domestic and Wild areas. Ant fauna was collected over a period of six months using an inline-fixing technique combined with pitfall traps and hand sampling. A total of 30 ant species were collected, belonging to 15 genera in four subfamilies: Formicinae, Myrmicinae, Dolichoderinae, and Dorylinae. The maximum population was recorded in the Wild area due to dense forest vegetation present at this station. The most abundantly found species in the Domestic area was Lasius niger, while Formica spp. was most common in the Wild area. Diversity (H) and Margalef Richness indices were recorded higher for the Wild habitat, while Evenness was found higher in the Domestic habitat. Statistical analysis showed that the abundance and species richness were highly significant for both habitats (p < 0.001). Ant populations showed significant variation with temperature and humidity; for example, an increase in temperature and low humidity favored the abundance of ants. Being the first such study in the region, the results add significantly to the understanding of this terrain’s ecology.